Measuring Anisotropy in Planar Sets - Toby C. O'Neil (Real analysis exchange, 2018)
We define and discuss a pure mathematics formulation of an approach proposed in the physics literature to analysing anistropy of fractal sets. Mathematical Reviews subject classification: Primary: 26A03, 26A04; Secondary: 26A05 Key words: anisotropic dimension spectrum, Hausdorff dimension, anisotropy